Tren Kasus Hipertensi Berdasarkan Data Pelayanan Kesehatan Primer dan Gambaran Perilaku Merokok Rumah Tangga di Gampong Miruk Kabupaten Aceh Besar - Ully Fitria; Srie Wahyuni; Dian Rahayu; Saila Anggraini; Safrizal Safrizal; Rina Andriani; Ratika Nuri; Masfina Masfina; Putri Maulidia; Ahmad Muhajir (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Hypertension is a major public health problem and contributes to an increased risk of cardiovascular disease. Routine primary health care data can provide information on the development of hypertension cases and support evidence-based promotive and preventive strategies. This study aimed to describe the trend of identified hypertension cases based on primary health care data and to describe household smoking behavior in Gampong Miruk, Aceh Besar Regency. A retrospective descriptive design was used with secondary data from First-Level Outpatient Care reports at the Gampong Miruk Polindes for 2024–2025, community health screening data for 2026, and the 2025 household Clean and Healthy Living Behavior survey. Data were analyzed descriptively using frequencies, percentages, and trend presentation. The number of identified hypertension cases increased from 6 cases in 2024 to 8 cases in 2025 and 18 cases in 2026. However, the increase in 2026 should be interpreted cautiously because the data were obtained through community health screening, which had broader detection coverage than routine service records. The household survey showed that 81 of 105 households (77.1%) did not meet the indicator of not smoking inside the house, while 24 households (22.9%) met the indicator. These findings indicate that hypertension and household exposure to tobacco smoke require attention in Gampong Miruk. Strengthening periodic hypertension screening, family-based health promotion, and smoke-free home initiatives is recommended as part of community-level noncommunicable disease prevention and control.